2006
DOI: 10.1016/j.molcel.2006.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Termination and Nuclear Degradation of Cryptic Unstable Transcripts: A Role for the Nrd1-Nab3 Pathway in Genome Surveillance

Abstract: Cryptic unstable transcripts (CUTs) are widely distributed in the genome of S. cerevisiae. These RNAs generally derive from nonannotated regions of the genome and are degraded rapidly and efficiently by the nuclear exosome via a pathway that involves degradative polyadenylation by a new poly(A) polymerase borne by the TRAMP complex. What is the share of significant information that is encrypted in CUTs and what distinguishes a CUT from other Pol II transcripts are unclear to date. Here we report the dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
225
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(232 citation statements)
references
References 35 publications
6
225
0
1
Order By: Relevance
“…Alternatively, the recruitment of the exosome could be constitutive and independent of specific processing events. For instance, the degradation of cryptic unstable transcripts in S. cerevisiae is closely coupled to the Nrd1p-Nab3p-dependent transcription termination pathway (Arigo et al, 2006;Thiebaut et al, 2006). Our results suggest, in contrast, that protein-coding genes in insects are monitored by a constitutive mechanism.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, the recruitment of the exosome could be constitutive and independent of specific processing events. For instance, the degradation of cryptic unstable transcripts in S. cerevisiae is closely coupled to the Nrd1p-Nab3p-dependent transcription termination pathway (Arigo et al, 2006;Thiebaut et al, 2006). Our results suggest, in contrast, that protein-coding genes in insects are monitored by a constitutive mechanism.…”
Section: Discussionmentioning
confidence: 77%
“…These transcripts are estimated to originate from 10% of yeast intergenic regions (Wyers et al 2005; although see Neil et al 2009 andXu et al 2009). After Nrd1-dependent termination by RNAPII, CUTs are rapidly polyadenylated by the TRAMP complex, and then degraded by the nuclear exosome (Wyers et al 2005;Arigo et al 2006b;Houalla et al 2006;Thiebaut et al 2006). Recently, Gudipati et al (2008) showed that Nrd1-dependent termination of CUTs is inhibited by CTD phosphorylation on Ser2 and promoted by Ser5 phosphorylation.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…It has recently been shown that the RNA-binding proteins Nrd1 and Nab3 interact with the nuclear exosome and are required for the termination of RNAPII and cryptic unstable transcripts in yeast. [18][19][20] The wide variety of PAR types may in part reflect the diversity of cleavage, elongation, termination, and exosome components that form and interact with the RNAPII complex. Indeed, one of the most appealing aspects of a model of RNAPII-dependent small RNA biogenesis is that it Cell Cycle 2009; Vol.…”
Section: Tirnas In Plants and Nematodesmentioning
confidence: 99%